Water exchange reactions and hydrolysis of hydrated titanium(III) ions. A density functional theory study - Hartmann, Michael; Clark, Timothy; van Eldik, Rudi (Journal of Physical Chemistry A, 1999)
The structure and water exchange mechanism of hexahydrated Ti(III), its hydrolysis, and the water exchange mechanism of analogous hydroxo-aqua complexes have been studied using density functional theory (DFT) calculations. Isolated metal-aqua and metal-hydroxo clusters corresponding to the gas-phase (T = 0 K) were used to approximate the model reactions. The structure of [Ti(H2O)(6)](3+) was found to have C-i symmetry and Ti-O bond lengths of 2.094 Angstrom. The water exchange reaction of this complex follows an (almost) limiting A mechanism with an energy of activation of 15.8 kcal mol(-1). The hydrolysis of hexahydrated Ti(III) was modeled by an in vacuo proton-transfer process between water molecules of the first and second coordination spheres of [Ti(H2O)(6)](3+).H2O. This process was found to be activationless and leads to the unusually stable dication:cation pair [Ti(H2O)(5)(OH)](2+).H3O+, which is lower in energy than the reactant by 4.5 kcal mol(-1). Only a weak structural influence, indicated by a slight increase in the mean value of the Ti-O bond lengths of water molecules in the first coordination sphere, is observed when the hydroxo ligand is formed. The water exchange reactions of the corresponding hydroxo-aqua complexes [Ti(H2O)(5)(OH)](2+) and [Ti(H2O)(5)(OH)](2+).H2O, respectively, were found to proceed via limiting D mechanisms. The energies of activation for the exchange of the water molecule in the trans-position to the hydroxo ligand were calculated to be only 9.8 and 7.2 kcal mol(-1), respectively. This, however, implies that the apparently weak influence of coordinated hydroxide still results in a significant reduction in the energy barrier for the water exchange reaction and also leads to a complete changeover in the preferred exchange pathway from A to D.